ELEMENTARY EFL TEACHERS’ KNOWLEDGE AND PRACTICES IN FOSTERING LEARNER AUTONOMY - Fadilla, Suci; Yusuf, Fazri Nur; Wirza, Yanty (Universitas Islam Sumatera Utara (UISU), 2025)
Learner autonomy is essential in young learners’ language development, yet its implementation remains limited at the elementary level, particularly in contexts rooted in teacher-centered traditions. This study examined the understanding of elementary EFL teachers and the strategies they use to foster learner autonomy in EYL classrooms in Indonesia, employing a sequential mixed-methods design. The study commenced with a survey of 34 teachers, followed by semi-structured interviews with four selected teachers. Descriptive statistics were used to analyze survey data, while thematic analysis was applied to interview transcripts. The findings revealed that most teachers have a positive understanding of learner autonomy, with a particular emphasis on their role as facilitators and motivators. Teachers applied various strategies to foster autonomy, such as providing choice in learning activities and giving positive feedback. However, this positive orientation was contrasted by the presence of teacher skepticism regarding young learners’ readiness for autonomy. These findings suggest that while the conceptual understanding of learner autonomy is present, its implementation still requires targeted professional development focusing on age-appropriate pedagogical scaffolding and practical tools to move teachers beyond conceptual understanding to consistent autonomous practice.